PROHIBITION OF THE USE OF FORCE BY NON-STATE ACTORS: IS IT TIME TO MOVE TOWARDS INTERNATIONAL REGULATION? - Ghazi Janaby, Mohamad (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article underscores the pressing need to expand the scope of theprohibition of the use of force principle, firmly established in internationallaw, to encompass non-state actors (NSAs). Conventional wisdom holdsthat the legality of employing force by NSAs within a specific state'sterritory is subject to domestic lawrather than international regulations.However, recent years have borne witness to an unprecedented surge inthe use of force by NSAs, resulting in consequences that transcend nationalboundaries. Notable examples include organisations such as ISIS, BokoHaram, and even private military companies like Wagner, the Russianprivate military company. Hence, it becomes pivotal to raise the question ofwhether international law should exert its influence over the conduct of NSAs.While international law does indeed govern the use of force by NSAs to someextent, particularly from a jus ad bellum perspective, this control remainsrather limited. This paper undertakes a comprehensive examination of thisissue and contends that international legal principles pertaining to theprohibition of the use of force should be extended to encompass NSAs,including the application of jus in bello principles.
Keywords: aggression; ISIS; occupation; armed attack